Organizational Semiotics and Participatory Design to Requirements Elicitation - A Case Study - Arantes, Flávia Linhalis (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2011)
It is already agreed that requirements have a critical impact on the quality and users satisfaction of the resulting software. In this work, web information systems are reviewed from the perspective of organizational semiotics as being part of an organization, which comprises work practices, rules and views of the same system by different stakeholders. This paper presents a case study, where artifacts of the organizational semiotics are exploited in a collaborative and participatory way to requirements elicitation of a web information system.